Intramedullary Conus Medullaris Tuberculoma: A Case Report and Review of the Literature - Verajit Chotmongkol; Chinadol Wanitpongpun; Warinthorn Phuttharak; Sittichai Khamsai (Infectious Disease Reports, 2021)
Intramedullary tuberculoma (IMT) of the conus medullaris is extremely rare. We present a case of intramedullary conus medullaris tuberculoma in which the diagnosis was based on there being very high levels of adenosine deaminase (ADA) in the patient’s cerebrospinal fluid (CSF) and improvement with antituberculous therapy. A 78-year-old man presented after having had a dull ache in both thighs and progressive paraparesis. The patient’s medical history included diffuse large B-cell lymphoma, which had undergone remission due to chemotherapy two years earlier, and long-term, well-controlled diabetes. A chest X-ray showed no evidence of tuberculosis. The results of CSF analysis were compatible with Froin’s syndrome. An initial diagnosis was made of an intramedullary tumor of the conus medullaris, based on magnetic resonance imaging (MRI). A myelotomy and multiple punch out biopsy were performed, and histopathology of the tissues revealed mild reactive gliosis. Due to the patient having high levels of CSF-ADA, IMT of the conus medullaris was suspected. The patient was treated with an 18-month course of antituberculous therapy. The dull ache gradually disappeared, and motor power improved slightly. A follow-up MRI of the lumbosacral (LS) spine revealed that the lesion had completely disappeared. Intramedullary tuberculoma of the conus medullaris should be considered in patients with underlying malignancy and no symptoms of systemic tuberculosis. CSF adenosine deaminase levels can be helpful in determining the presence of central nervous system tuberculosis when other systemic signs of disease are lacking.